2021
DOI: 10.3390/diagnostics11030541
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Osseous Morphology of Class I and Class II Malocclusions in the Normal Skeletal Pattern: A Cone-Beam Computed Tomography Study

Abstract: (1) Background—The aim of the present study was to evaluate the correlation between the temporomandibular joint (TMJ) osseous morphology of normal skeletal pattern individuals with different dental malocclusions by using cone-beam computed tomography (CBCT). (2) Methods—The CBCT images of bilateral TMJs in 67 subjects with skeletal class I and average mandibular angle (26 males and 41 females, age range 20–49 years) were evaluated in this study. The subjects were divided into class I, class II division 1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…28 The articular fossa limits the range of motion of the condyle. 29 In our study, the depth of the articular fossa and the degree of articular nodule was positively correlated with the condyle volume, which was consistent with the conclusion of previous studies that the articular fossa was correlated with the condyle size.…”
Section: Discussionsupporting
confidence: 93%
“…28 The articular fossa limits the range of motion of the condyle. 29 In our study, the depth of the articular fossa and the degree of articular nodule was positively correlated with the condyle volume, which was consistent with the conclusion of previous studies that the articular fossa was correlated with the condyle size.…”
Section: Discussionsupporting
confidence: 93%
“…In all studies, with one exception [22], the studied population consisted of both women and men. In half of the papers, the CBCT study was analyzed with more than 1 investigator [34,35,40,56,57,59,60]. The most commonly evaluated variables were the height and angle of the articular eminence and depth and width of the glenoid fossa.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Most often, a decrease in the angle of the articular eminence was observed compared to the control group in skeletal and dental class II malocclusions [34,57]. In contrary, Fan et al [59] presented in their study that class II/2 patients were associated with the highest articular eminence inclination. Gorucu-Coskuner et al [51] showed a deeper and wider glenoid fossa in class II division 1 malocclusions compared with skeletal class II division 2 groups.…”
Section: Tmj Articular Eminence and Mandibular Fossa Inmentioning
confidence: 90%
See 2 more Smart Citations